Total flavonoids of Oldenlandia diffusa (Willd.) Roxb. suppresses the growth of hepatocellular carcinoma through endoplasmic reticulum stress-mediated autophagy and apoptosis - Chen, Huan; Shang, Xiaofei; Yuan, Huixin; Niu, Qianqian; Chen, Jing; Luo, Shumin; Li, Weihua; Li, Xiuhui (Frontiers in Pharmacology, 2022)
Hepatocellular Carcinoma (HCC) is one of the most common malignant tumors in the world. Although the current treatment methods for HCC are gradually increasing, its efficacy still cannot meet the medical needs of patients with liver cancer, and new and effective treatment strategies are urgently needed. The total flavonoids of Hedyotis diffusa (FOD) are the main active components in Hedyotis diffusa, which have anti-inflammatory, antioxidant and anti-tumor effects, but their mechanism of action in liver cancer is unclear. In this study, we examined the effect of FOD on HCC. Using both in vitro and in vivo models, we confirmed that FOD inhibited HCC proliferation and induced apoptosis and autophagy. Mechanistic studies have shown that FOD induces apoptosis and activates autophagy in HCC cells by inducing endoplasmic reticulum stress (ER stress) and activating the PERK-EIF2α-ATF4 signaling pathway. Taken together, our results suggest that FOD is a potential anticancer drug targeting ER stress for the treatment of HCC.